Are part-time workers less productive and underpaid? - Andrea Garnero (IZA World of Labor, 2016)
About one in five workers across OECD countries is employed part-time, and the share has been steadily increasing since the beginning of the economic and financial crisis in 2007. Part-time options play an important economic role by providing more flexible working arrangements for both workers and firms. Part-time employment has also contributed substantially to increasing the employment rate, especially among women. However, part-time work comes at a cost of lower wages for workers, mainly because part-time jobs are concentrated in lower paying occupations and sectors, while the impact on firms' productivity is still not very clear.
Keywords: J22; J24; J31; J70; 330; part-time workers; productivity; wage gap; labor market segregation; labor market flexibility; work-life balance